Performance of VIA (Visual Inspection with Acetic Acid) and Coloposcopic Biopsy as a Method of Screening in Detecting Preinvasion and Early Cancerous Lesion of the Cervix (Medicine Today, 2012)
Medicine Today 2011 Volume 23 Number 01 Page 13-17 DOI: http://dx.doi.org/10.3329/medtoday.v23i1.11938